2008
DOI: 10.1243/09576509jpe662
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of impeller—diffuser interaction in a centrifugal compressor with different types of diffusers

Abstract: A computational study has been conducted to analyse the performance of a centrifugal compressor with different types of diffusers under various levels of impeller—diffuser interactions. Vaneless (VLD), vaned (VD), low solidity vaned (LSVD), and partial vaned diffusers (PVD) are used for this purpose. The study is carried out using commercial software ANSYS CFX. The interaction level is varied by varying the radial gap between the impeller and diffuser by keeping the diffuser vane at three different radial loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Following [11][12][13][14] the k-SST model was selected. The chosen k-SST model is widely used and has been validated for turbomachinery applications [20].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following [11][12][13][14] the k-SST model was selected. The chosen k-SST model is widely used and has been validated for turbomachinery applications [20].…”
Section: Methodsmentioning
confidence: 99%
“…Out of the accumulation of a body of work, a number of common approaches have resulted in terms of CFD model settings with regard to turbulence models [11][12][13][14], interface settings [4,6,7,9,[15][16][17], and boundary conditions [7,11,18]. There are a number of turbulent models which can be applied in a RANS simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time step was taken to be the time of an impeller blade passing 1/360 of a circle. This value is the optimum time step according to Anish and Sitaram (2009) and Anish et al (2014). The 'stage' method (ANSYS, 2011a) was adopted for analyzing the IDIs for steady simulations.…”
Section: Numerical Schemementioning
confidence: 99%
“…Hosseini, Sun, He, and Zheng (2017) achieved a radial clearance ratio that yielded the best pressure recovery coefficient, loss coefficient, and grade efficiency when M u ≥ 1. Optimal radial clearance exists for specific working conditions (Krishnababu, Imregun, Green, & Hoyniak, 2010;Anish & Sitaram, 2009). Robinson, Casey, Hutchinson, and Steed (2012) reported that decreasing the radial clearance ratio substantially increased efficiency.…”
Section: Introductionmentioning
confidence: 99%